2007
DOI: 10.1590/s1517-86922007000100012
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre a atividade EMG do peitoral maior, deltóide anterior e tríceps braquial durante os exercícios supino reto e crucifixo

Abstract: The identification of the characteristics of each movement and its adjustment to the training goals are tasks that demand the interaction of many knowledge areas. These tasks are essential to the success in sports activities and training programs designed with athletic, aesthetic or healthy purposes. The objective of the present study was to compare the electromyographic (EMG) activity of the pectoralis major (PM), anterior deltoids (DA) and triceps brachii (TB) muscles during the barbell bench press (SP) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
1
2
0
4
Order By: Relevance
“…For the triceps brachii, it can be speculated that the set-volume ratio of MJ:SJ may be a bit lower than for the biceps, particularly for the long head of the triceps. This notion is consistent with the combination of muscle biomechanics theory, EMG data [37,38], and longitudinal studies showing greater growth in the long head when using the lying triceps extension (i.e., SJ exercise) vs. the bench press (i.e., MJ exercise) [44,45]. The same extrapolations may apply to the quadriceps muscle given some of the EMG data showing higher amplitude during the performance of a SJ exercise, particularly in the rectus femoris.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For the triceps brachii, it can be speculated that the set-volume ratio of MJ:SJ may be a bit lower than for the biceps, particularly for the long head of the triceps. This notion is consistent with the combination of muscle biomechanics theory, EMG data [37,38], and longitudinal studies showing greater growth in the long head when using the lying triceps extension (i.e., SJ exercise) vs. the bench press (i.e., MJ exercise) [44,45]. The same extrapolations may apply to the quadriceps muscle given some of the EMG data showing higher amplitude during the performance of a SJ exercise, particularly in the rectus femoris.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported ~twofold greater myoelectric activity of the pectoralis major compared to the triceps brachii during performance of the bench press [37,38]. Similarly, the lat pulldown and seated row result in greater myoelectric activity in the latissimus dorsi compared to the biceps brachii, although the disparity in EMG amplitude between muscles diminishes when a supinated grip is employed [39,40].…”
Section: Acute Studiesmentioning
confidence: 99%
“…Deste modo, os estudos relacionados ao sistema muscular, se tornaram mais significativos e interessantes, pois percebemos com maior clareza a aplicabilidade da EMG que pode ser dirigida ao tempo de reação muscular , a ativação de diferentes grupos musculares em um determinado movimento (BANDEIRA, BERNI, RODRIGUES, 2009) e também na averiguação da fadiga (BASSANI et al, 2008). Com isso, é possível utilizar a EMG para diferentes finalidades, partindo de estudos relacionados a gestos de exercícios físicos ou esportivos (ROCHA JUNIOR et al, 2007;SUDA, CANTUÁRIA, SACCO, 2008) indo até a aplicação em pesquisas com enfoque na saúde (BASSANI et al, 2008;BEVILAQUA, FELÍCIO, LEOCÁDIO, 2008). Segundo De Luca (1997) (2005).…”
Section: Introductionunclassified
“…Deste modo, os estudos relacionados ao sistema muscular, se tornaram mais significativos e interessantes, pois percebemos com maior clareza a aplicabilidade da EMG que pode ser dirigida ao tempo de reação muscular , a ativação de diferentes grupos musculares em um determinado movimento (BANDEIRA, BERNI, RODRIGUES, 2009) e também na averiguação da fadiga (BASSANI et al, 2008). Com isso, é possível utilizar a EMG para diferentes finalidades, partindo de estudos relacionados a gestos de exercícios físicos ou esportivos (ROCHA JUNIOR et al, 2007;SUDA, CANTUÁRIA, SACCO, 2008) indo até a aplicação em pesquisas com enfoque na saúde (BASSANI et al, 2008;BEVILAQUA, FELÍCIO, LEOCÁDIO, 2008). Segundo De Luca (1997) a EMG pode ser aplicada para identificar o momento de ativação dos músculos, para a análise de força, e também na detecção da fadiga muscular.…”
Section: Introductionunclassified